Which animal-to-feeding-place ratio at time-controlled hay racks is animal appropriate? Preliminary analysis of stress responses of horses - Baumgartner, Miriam; Erhard, Michael H.; Zeitler-Feicht, Margit H. (Frontiers in Veterinary Science, 2023)
Automated feeding systems offer numerous advantages for animals and humans, but the associated benefits and risks can often only be seen under practical conditions. The space allowance (approximately 80 cm per horse) at time-controlled hay racks for horses in group housing, unlike at partitioned feeding stands or transponder-controlled feed stations, currently falls below the required individual distance between the horses, which can result in a high level of aggression between the horses due to the lack of partitions between them. Hence, a feed-through at a time-controlled hay rack cannot be equated with a feeding place. In this preliminary study, we therefore aimed to determine the minimum animal-to-feeding-place ratio (AFR) at time-controlled hay racks that would provide adequate individual distances between the horses. To do so, we assessed behavioral and physiological parameters (via video behavioral observations and salivary cortisol measurements) of up to 28 horses in a loose housing system. Over two observation days per treatment, four AFRs were investigated in a balanced sequence: 1:1.2, 1:2, 1:3, and C (single feeding in familiar surroundings as a control). We found that the horses expressed less aggressive behavior, especially those behaviors with a high risk of injury such as biting and kicking, when there were three times as many openings as there were horses at time-controlled hay racks, as compared with only 20% more openings or twice as many openings as there were horses (lineal mixed model: F(3,4) = 7.411; adjusted R2 = 0.733; p(AFR_1:2) = 0.06, p(AFR_1:3) = 0.02, p(AFR_C) = 0.01). The salivary cortisol levels during feeding decreased more strongly with more generous AFRs (p(AFR_metric) = 0.02). The factors hierarchy and individual showed no influence. In contrast, the day of the experiment and the associated weather conditions, despite randomized selection, influenced both the behavioral and the physiological parameters. The results of this preliminary study indicate that the investigated time-controlled hay racks must provide at least three times as many feeding places as there are horses to ensure that neighboring horses can keep their individual distance and stress-free feeding is possible. Further studies on more farms and different hay racks are proposed.